2021
DOI: 10.4274/tjo.galenos.2021.49323
|View full text |Cite
|
Sign up to set email alerts
|

Serpiginous Choroiditis Complicated with Choroidal Neovascular Membrane Detected using Optical Coherence Tomography Angiography: A Case Series and Literature Review

Abstract: Serpiginous choroiditis (SC) is a rare, chronic, recurrent, progressive disease of unknown origin. The inflammatory process of SC can disrupt Bruch’s membrane, allowing occasional choroidal vascular growth, leading to significant visual loss even in the healed stages of the disease. Optical coherence tomography angiography (OCTA) can help in the detection of choroidal neovascular membrane (CNV), leading to a definitive diagnosis and thereby guide the initiation of intravitreal anti-vascular endothelial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…OCT-A was shown to be useful and a help in the detection of choroidal neovascularization (CNV) such as in MFC/PIC and other choriocapillaritis entities as well as its followup during anti-VEGF treatment but none of the articles recommended it as an exclusive use. [29][30][31][32][33][34] One report indicated that OCT-A could possibly better identify new vessels obscured by retinal haemorrhage [35]. OCT-A has been reported to be useful to distinguish CNV from active uveitic lesions [36].…”
Section: Optical Coherence Tomography Angiography (Oct-a)mentioning
confidence: 99%
“…OCT-A was shown to be useful and a help in the detection of choroidal neovascularization (CNV) such as in MFC/PIC and other choriocapillaritis entities as well as its followup during anti-VEGF treatment but none of the articles recommended it as an exclusive use. [29][30][31][32][33][34] One report indicated that OCT-A could possibly better identify new vessels obscured by retinal haemorrhage [35]. OCT-A has been reported to be useful to distinguish CNV from active uveitic lesions [36].…”
Section: Optical Coherence Tomography Angiography (Oct-a)mentioning
confidence: 99%